Kinetics of Oxidation Decarboxylation of β-Benzoylpropionic Acid by Manganese (III) Acetate - Sikkander, G. (Asian Journal of Chemistry, 2010)
The kinetics of oxidative decarboxylation of β-benzoylpropionic acid by manganese(III) acetate in aqueous acetic acid medium have been studied. The reaction is first order each in [substrate], [oxidant] and [H+] ion. The effects of solvent polarity and temperature on the rate of oxidation have been measured. Activation parameters are evaluated and a suitable mechanism consistent with the experimental results has been proposed.